Exploitation of Natural By-Products for the Promotion of Healthy Outcomes in Humans: Special Focus on Antioxidant and Anti-Inflammatory Mechanisms and Modulation of the Gut Microbiota - Luigi Santacroce; Lucrezia Bottalico; Ioannis Alexandros Charitos; Francesca Castellaneta; Elona Gaxhja; Skender Topi; Raffaele Palmirotta; Emilio Jirillo (MDPI AG, 2024)
Daily, a lot of food is wasted, and vegetables, fruit, and cereals as well as marine products represent the major sources of unwanted by-products. The sustainability, waste recovery, and revalorization of food by-products have been proposed as the main goals of the so-called circular economy. In fact, food wastes are enriched in by-products endowed with beneficial effects on human health. Grape, olives, vegetables, and rice contain different compounds, such as polyphenols, dietary fibers, polysaccharides, vitamins, and proteins, which exert antioxidant and anti-inflammatory activities, inhibiting pro-oxidant genes and the Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-kβ) pathway, as demonstrated by in vitro and in vivo experiments. Dietary fibers act upon the gut microbiota, expanding beneficial bacteria, which contribute to healthy outcomes. Furthermore, marine foods, even including microalgae, arthropods, and wastes of fish, are rich in carotenoids, polyphenols, polyunsaturated fatty acids, proteins, and chitooligosaccharides, which afford antioxidant and anti-inflammatory protection. The present review will cover the major by-products derived from food wastes, describing the mechanisms of action involved in the antioxidant and anti-inflammatory activities, as well as the modulation of the gut microbiota. The effects of some by-products have also been explored in clinical trials, while others, such as marine by-products, need more investigation for their full exploitation as bioactive compounds in humans.